2017
DOI: 10.1124/mol.116.107854
|View full text |Cite
|
Sign up to set email alerts
|

GABABR-Induced EGFR Transactivation Promotes Migration of Human Prostate Cancer Cells

Abstract: G protein-coupled receptors (GPCRs) and receptor tyrosine kinases (RTKs) act in concert to regulate cell growth, proliferation, survival, and migration. Metabotropic GABA receptor (GABAR) is the GPCR for the main inhibitory neurotransmitter GABA in the central nervous system. Increased expression of GABAR has been detected in human cancer tissues and cancer cell lines, but the role of GABAR in these cells is controversial and the underlying mechanism remains poorly understood. Here, we investigated whether GAB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 65 publications
0
25
1
1
Order By: Relevance
“…In contrast, other studies revealed that GABA B receptor activation promoted the invasive ability of prostate and renal cancer cells (Azuma et al, 2003;Inamoto et al, 2007) and the metastasis of mouse breast 4T1 cancer cells (Zhang et al, 2014). We have also recently reported that GABA B receptor induced epidermal growth factor (EGFR) transactivation and promoted the invasion of human prostate cancer cells (Xia et al, 2017). GABA B receptor is a G-protein-coupled receptor (GPCR) and is composed of GABA B1 (GB 1 ) and GABA B2 (GB 2 ) subunits (Pin et al, 2004), encoded by the GABBR1 and GABBR2 genes, respectively.…”
Section: Introductionmentioning
confidence: 71%
“…In contrast, other studies revealed that GABA B receptor activation promoted the invasive ability of prostate and renal cancer cells (Azuma et al, 2003;Inamoto et al, 2007) and the metastasis of mouse breast 4T1 cancer cells (Zhang et al, 2014). We have also recently reported that GABA B receptor induced epidermal growth factor (EGFR) transactivation and promoted the invasion of human prostate cancer cells (Xia et al, 2017). GABA B receptor is a G-protein-coupled receptor (GPCR) and is composed of GABA B1 (GB 1 ) and GABA B2 (GB 2 ) subunits (Pin et al, 2004), encoded by the GABBR1 and GABBR2 genes, respectively.…”
Section: Introductionmentioning
confidence: 71%
“…Both receptors mediate important signaling events and are involved in various complex physiological processes including cellular growth and differentiation (Wang et al, 2018). It was found that GPCRs could activate RTKs in the absence of RTK ligands (Delcourt et al, 2007), a phenomenon called transactivation (Crudden et al, 2018; Xia et al, 2017). The activation of EGFR main downstream signal pathway is closely related to the drug resistance mechanism of EGFR monoclonal antibodies (Zhang et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Further, GPCRs can utilize receptor tyrosine kinases (RTKs) to mediate important cellular responses, such as proliferation, differentiation, and survival [ 8 ]. Depending on the receptor and cell type, GPCRs signaling involves transactivation of several different RTKs, such as insulin-like growth factor 1 receptor (IGF1R), epidermal growth factor receptor (EGFR), and platelet-derived growth factor receptor (PDGFR) [ 9 , 10 , 11 ]. Then, numerous growth factors use G proteins and associated signaling molecules that participate downstream of RTKs to signal to effectors.…”
Section: Structure and Signal Transduction Of G Protein-coupled Rementioning
confidence: 99%